EFFECTIVENESS OF MINDFULNESS MEDITATION ON PERCEIVED STRESS AND COPING STRATEGIES AMONG B.SC NURSING STUDENTS IN TIRUVANNAMALAI DISTRICT: A RANDOMIZED CONTROLLED TRIAL - Mrs.ABIRAMI. S,; Dr. VASANTHA (The Bioscan, 2025)
Nursing students often experience high levels of stress during their education and clinical training, which can negatively impact their academic performance and wellbeing. Managing stress and maintaining mental health require effective coping strategies for these students. Many populations, including nursing students, have shown that mindfulness meditation reduces stress and improves coping strategies. It aims to evaluate mindfulness meditation in the context of a B.Sc Nursing program in Kanchipuram District, as well as to assess perceived stress levels and coping strategies among these students. The study consisted of 200 nursing students in two groups, a control group and a study group. A paired t-test and a chi-square test were used to analyze the data in the study. Study results showed that mindfulness meditation significantly reduced perceived stress levels and improved coping strategies among the study group when compared to the control group. Among nursing students, mindfulness meditation might be beneficial in managing stress, according to the results of the study.